PENENTUAN TOTAL SENYAWA FENOLAT DAN AKTIVITAS ANTIOKSIDAN PADA ASAP CAIR DARI AMPAS TEBU DAN KULIT TEBU (Sacharum Officinarum) SERTA IDENTIFIKASI KOMPONEN PENYUSUNNYA - ., Sulistiyowati (Chem Info Journal, 2013)
Abstract: Sugarcane (Saccharum officinarum) is a plant that is grown for raw sugar, not only for raw sugar, but it could be material for liquid smoke. A study concerning the determination of total phenolic compounds and antioxidant activity of liquid smoke sugarcane pulp and cane skin as well as the identification of its constituent components. This research was conducted to determine levels of total phenolic compounds, antioxidant activity and identification of chemical components in the liquid smoke from sugarcane pulp and sugarcane skin. Liquid smoke is made by means of pyrolysis. Pyrolysis is the thermal degradation of organic materials decompose at high temperatures in the absence of oxygen. One of the processes that result in degradation of the lignin phenolic compounds. The content of total phenolics was determined using the Folin Ciocalteu reagent were expressed as the number of mg gallic acid equivalents per g of extract. antioxidant activity assay by the method of DPPH (1,1-diphenyl-2-picrylhydrazyl) and the identification of its constituent components using GCMS. The results showed levels of total phenolic compounds for liquid smoke sugarcane pulp and cane skin respectively 68.083 mg GE / g and 171.417 mg GE / g liquid smoke, as well as price IC50 of each sample at 283.586 ppm and 216.58 ppm. The identification of its constituent components using GCMS both samples have the same dominant compounds are phenol, furan, acetic acid and syringol.